Efeito do fortalecimento de músculos do quadril e tronco sobre a cinemática dos membros inferiores durante a descida de degrau - Vanessa Lara de Araujo (2013)
Introduction:During closed kinematic chain activities, such as stair descent, the movements of hip medial rotation and adduction are often coupled to medial rotation and adduction of the thigh, displacement of the knee joint toward the bodys midline (dynamic knee valgus), medial rotation of the shank and pronation of the ankle-foot complex (AFC). The excess of these movements is commonly related to the occurrence of musculoskeletal injuries. The capacity of the hip structures to actively and/or passively resist medial rotation and adduction of this joint may be crucial to control excessive movement of the hip, knee and AFC in the frontal and transverse planes. Furthermore, considering the existence of connections between bodys tissuesand segments, muscles of the trunk can also influence the kinematics of the lower limbs. Objectives:(1) To investigate the effect of a strengthening program of hip muscles (abductors and lateral rotators) and trunk muscles (latissimusdorsi and lateral flexors and rotators of the trunk) on muscle performance and onpassive properties of the hip joint in healthy women; (2) To investigate the effect of this program on the kinematics of the lower limb in the frontal and transverse planes during a single limb step down. Materials and method: An experimental study was carried out with 34 women. Seventeen participants were allocated in the experimental group (age of 22.41 ± 3.81 years and BMI of 21 ± 1. 45 kg/m2) and 17 in the control group (21.71 ± 2.08 age years and BMI 19.99± 2.26 kg/m2). The experimental group performed three weekly sessions of high loading strengthening of the hip and trunk muscles for eight weeks. The individuals of the control group were instructed to continue theirnormal activities during this period. Before and after the intervention period, the participants were subjected to the following tests: (1) evaluation of maximum concentric and eccentric work of the hip lateral rotators muscles at an isokinetic dynamometer; (2) evaluation of hip passive torque and resting position during medial rotation of this joint at the isokinetic dynamometer and (3) three-dimensional kinematic assessment of the pelvis, thigh, shank, rearfoot and forefoot during step down task. Mixed design analyses of variance (ANOVAs) with one between-subject effect (experimental and control groups) and one within-subject effect (pre- and post-training) were used to investigate the effect of strengthening program on active and passive variables measured at the isokinetic dynamometer. For the kinematic data, the statistical analysis was made by comparing the curves obtained on the assessment and reassessment for each angle analyzed. At each percentage of the step-down cycle, confidence intervals (95% CI) were calculated for the differences between the angular positions of the curves obtained in the evaluation and reevaluation. The significance level was set at 0.05 for all analyses. Results:The variables related to the maximum performance of hip muscles demonstrated significantmain effect for group X condition interaction (p < 0.001) in mixed ANOVAs. The contrasts showed that the strengthening program increased the maximum concentric (p < 0.001) and eccentric work (p < 0.001) of the hip lateral rotators. Regarding thepassive torque, the mixed ANOVA revealed significant main effect for condition (p = 0.024), i.e., significant increase was observed in the passive torque only when the participants of control and experimental groupswere analyzed together. The analysis of hip resting position showed significantmain effect for group X condition interaction (p = 0.026), and the comparison between pre- and post-training conditions indicated that the strengthening program shifted the hip resting position in the direction of lateral rotation (p < 0.001). Regarding the kinematic variables, it was observed that the strengthening program decreased adduction of the hip (93 to 100% of the period of the step down task), the thigh (96 to 100%) and the shank (0 to 95% and 98 to 100%), as well as, decreased the eversion of the forefoot in relation to the shank (0 to 35%). In the control group, there was a reduction of hip medial rotationat the moment of 91% of the period of the step down task. As the difference wasobserved in a single instant, it was considered of little relevance. Conclusion:The strengthening program increased the concentric and eccentric maximum workof the hip muscles and shifted the hip resting position. Furthermore, thisprotocol reduced lower limb adduction and AFC pronation during single limb stepdown task.